1980
DOI: 10.1254/jjp.30.689
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor Blocking Activity of Sulpiride in the Canine Exocrine Pancreas

Abstract: Abstract-The inhibitory effect of sulpiride on dopamine receptors was investigated in the exocrine pancreas of dogs anesthetized with pentobarbital and with the stomach ligated at the pylorus. All test substances were given intravenously. Dopamine, acetylcholine, histamine and secretin produced a dose-related increase in pancreatic juice secretion, though the dose-effect curves of these secretagogues differed in shape. Epinephrine, norepinephrine, isoproterenol, methamphetamine and serotonin had no secretagogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The stimulatory effect of histamine on pancreatic secretion is well established in several species [5,[31][32][33]. This study is in partial agreement with a previous report showing that the stimulatory effect of histamine is mediated by H1 receptors [1].…”
Section: Discussionsupporting
confidence: 92%
“…The stimulatory effect of histamine on pancreatic secretion is well established in several species [5,[31][32][33]. This study is in partial agreement with a previous report showing that the stimulatory effect of histamine is mediated by H1 receptors [1].…”
Section: Discussionsupporting
confidence: 92%
“…Exogenous application of histamine seems to have stimulatory effects on pancreatic secretion in dog (Tankel, Lester, Richman & Hollander, 1957;Lorenz et al 1968;Satoh, Satoh & Honda, 1980), pig (Hickson, 1970) and in vitro rabbit pancreas (Liebow & Franklin, 1982). It has also been demonstrated that histamine increases dog pancreatic secretion by activation of H2 receptors on pancreatic cells (Iwatsuki, Ikeda & Chiba, 1981).…”
Section: Introductionmentioning
confidence: 98%
“…In both the anaesthetized dog [32] and isolated dog pancreas [31], cimetidine and metiamide can completely inhibit the secretory action of histamine. In another study employing conscious dogs, cimetidine has been shown to decrease postprandial juice flow and bicarbonate output but increase amylase and protein output [65].…”
Section: Effects Of Selective Histaminergic Agonists and Antagonistsmentioning
confidence: 98%
“…It is similar in efficacy as secretin but slightly more potent than comparable stimulant as vasoactive intestinal polypeptide (VIP) [29,30]. Histamine can stimulate pancreatic juice secretion in the isolated dog pancreas [31], the anaesthetized dog [32,33], rabbit and guinea-pig [23,[34][35][36] but it is less effective as a secretagogue in the anaesthetized rat [37] and conscious dog [38]. In the in vitro pancreatic lobules of rabbit [28], segments of guinea pig [39,40] and rat [41] histamine can evoke marked increases in amylase secretion.…”
Section: Effect Of Histaminementioning
confidence: 99%